Carbon sequestration efficiency of mango-based agri-horticulture system in Shiwalik plain of Central Himalaya, India - Adhikari, Bhawna; Lodhiyal, Neelu; Lodhiyal, L.S. (Indian Journal of Agroforestry, 2019)
This paper deals with biomass, productivity and carbon efficiency of agri-horticulture system of Shiwalik plain of Central Himalaya. The study was conducted in mango-based agroforestry system with two different cropping pattern i.e. mango (Mangifera indica) + wheat (Triticum aestivum) and mango + black bhatt (Glycine max). The cereal crop (wheat) and pulse crop (black bhatt) were cultivated under mango trees in winter and rainy seasons, respectively. The biomass and productivity of fruit tree component was estimated by using the regression equation of respective component. The carbon potential was determined by using standard factor. The above-ground biomass and carbon stock was maximum (127 t ha-1 and 60.3 t C ha-1) in mango+wheat as compared to mango+black bhatt (123 t ha-1and 58.4 t C ha-1). The wheat and black bhatt under mango-based agri-horticulture system shared 4.3 and 1.2% of the total biomass and carbon stock of agroforestry system which was less than sole system (i.e. 6.24 and 1.58 t ha-1 biomass and 2.96 and 0.75 t C ha-1 carbon stock). Net primary productivity and carbon sequestration of mango was 16.09 t ha-1 yr-1 and 7.64 t C ha-1 yr-1, while long lived carbon storage, heat from biomass combustion and carbon storage from coal substitute was 10.90 t C ha-1, 1235.2 x 109 J t-1 and 20.75 t C ha-1, respectively. Thus, it is concluded that biomass production and carbon potential varied with cropping system orcrop combination. Moreover, the agroforestry system has high potential of biomass productivity and carbon efficiency than sole system. Therefore, the adoption of such land-uses is not only more profitable to the growers but also plays a significant ecological role in terms of carbon mitigation.